Balance assessment in the management of sport-related concussion - Guskiewicz, K. M. (Clinics in Sports Medicine, 2011)
Concussions remain a serious public health concern, with approximately 1.6 million to 3 million sport and recreational traumatic and brain injuries occurring every year in the United States. Most research on concussions has been conducted on male athletes, specifically, football players. However, female sport participation has steadily increased over the past decade. Recent studies suggest that the incidence of and recovery from sport-related concussion varies between male and female athletes, with women having a higher risk of sustaining a concussion and taking a longer time to recover than men. As a result, this article addresses the role of gender in the assessment and management of sport-related concussion.